Safety assessment of the process Arcoplastica, based on the Bandera PURe 15 technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials; Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Arcoplastica (EU register number RECYC308), which uses the Bandera PURe15 technology. The input consists of hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from post‐consumer PET containers, with no more than 5% PET from non‐food consumer applications. The flakes are ■■■■■. Having examined the challenge test provided, the Panel concluded that the ■■■■■ are critical for the decontamination efficiency. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature or below, with or without hotfill. The final articles made of this recycled PET are not intended to be used in microwave and conventional ovens, and such uses are not covered by this evaluation.